Effects of Pretreatments on Yields, Selectivity and Properties of Products from Pyrolysis of Phragmites Australis (Common Reeds) - Garrido-Lazo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
Phragmites australis (PHA) is a grass-type biomass, commonly known as reed grass, which has the potential to be a valuable energy and chemical feedstock due to its high yield (4.5–7 kg biomass m−2 year−1). It is demonstrated that the physicochemical properties and composition of phragmites can be altered by subjecting the feedstock to a combined acid hydrolysis at various level of acid concentrations and torrefaction pre-treatment processes. In this paper, we conducted fast pyrolysis on pretreated PHA, resulting in bio-oil with significantly higher selectivity towards levoglucosenone and appreciably reduced amounts of ketones and aldehydes being produced. The experiments demonstrated that 4% H3PO4 acid hydrolysis and 220◦C torrefaction combined pretreatments prior to fast pyrolysis resulted in 17 times increase of relative selectivity to levoglucosenone in the bio-oil portion along with a reduction of ketones and aldehydes relative concentrations from 23% to 13%. Pyrolysis of pretreated PHA produced higher amount of biochar. The phosphorus-enriched biochar offers a potential usage for soil amendment or sorbent material. This study presents an opportunity to convert this underutilized feedstock into valuable bio-based products. Additional in-depth investigation is essential to gather more data for assessing the economic and sustainability features of the proposed process. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.